ANALISIS FINANSIAL SISTEM USAHATANI TERPADU (INTEGRATED FARMING SYSTEM) BERBASIS TERNAK SAPI DI KABUPATEN OGAN ILIR - Idham Alamsyah; Tri Lestari; Dessy Adriani (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The objectives of this research are 1) to calculate the investment cost and operational cost which used by the company in production of integrated farming system based on cattle breeding, 2) to analyze the financial feasibility of integrated farming system based on cattle breeding, 3) to identified the most sensitive factors which influenced the financial feasibility of integrated farming based on cattle breeding. From the result of this research, know that the investment cost of integrated farming system based on cattle breeding is Rp5.043.254.000,00 and the operational cost is Rp14.276.416.000,00. The financial feasibility analysis of integrated farming system based on cattle breeding net B/C is 2,59, NPV is Rp4.676.889.872,19 and IRR is 30 percent. Sensitivity analysis of integrated farming system based on cattle breeding done from the input increasing such as the increasing of cattle breeding purchasing cost, the output decresing such as the decreasing of cattle breeding price selling, the production of cattle breeding can’t be reach, and also the sensitivity analysis done from both side together such as the increasing of cattle breeding purchasing cost together with the decreasing of cattle breeding output price selling, increasing of cattle breeding purchasing cost together with the decreasing of cattle breeding output price selling and the production of cattle breeding can’t be reach. The tolerance limit of the increasing of cattle breeding purchasing cost is 10,47 percent, the tolerance limit the decreasing of cattle breeding price selling is 8,68 percent, the tolerance limit of the production of cattle breeding can’t be reach is 8,68 percent, the tolerance limit of the increasing of cattle breeding cost together with the decreasing of cattle breeding price selling is 4,75 percent, an also the tolerance limit increasing of cattle breeding purchasing cost together with the decreasing of cattle breeding output price selling and the production of cattle breeding can’t be reach is 1,50 percent.